Comparison of Milligan-Morgan Haemorrhoidectomy versus Laser Haemorrhoidoplasty in Patients with Grade II and III Haemorrhoids: A Prospective Observational Study - Asfar Ahamed Nawabjan; Sathish Rajkumar; Chudar Arumugam; Mohamed Marzook; Jasmine Sharmila; Lalith Kumar (Journal of Clinical and Diagnostic Research)
Introduction: Haemorrhoidal disease results from abnormal dilation of anal cushions, influenced by dietary habits and pelvic anatomy. Surgical management remains essential for symptomatic cases, with Milligan-Morgan haemorrhoidectomy as the gold standard despite significant postoperative pain. Laser haemorrhoidoplasty has emerged as a minimally invasive alternative with faster recovery and fewer complications. Aim: To compare the clinical outcomes of Milligan-Morgan haemorrhoidectomy and laser haemorrhoidoplasty in patients with grade II and III haemorrhoids, focusing on postoperative pain, hospital stay, complications, and recovery time. Materials and Methods: A prospective observational study was conducted in the Department of General Surgery at Sri Lalithambigai Medical College and Hospital, Chennai, Tamil Nadu, India, from January 2022 to June 2023 (including three months of follow-up). A total of 40 patients were randomly assigned into 2 groups, group A (laser) with 20 patients and group B (Milligan Morgan) with 20 patients. The postoperative outcomes, including duration of intervention, pain, hospital stay, return-to-work time (recovery time) were assessed. Statistical analysis was performed using Statistical Package For Social Sciences (SPSS) software, with p<0.05 considered significant. Results: The mean age of the study participants was 41.35±13.95 in the laser group vs 43.3±12.75 in the open group, with no significant age or sex difference. The laser group had significantly lower postoperative pain {Visual Analogue Scale (VAS) 4.60±1.14 vs. 9.15±0.67 on Day 1, p<0.001}, shorter operative time (19.85 min vs. 54.75 min), reduced intraoperative blood loss (7±2.51 mL vs. 23±5.23 mL, p<0.001), and shorter hospital stay (1.1 vs. 1.85 days, p<0.001). Recovery time was significantly faster in the laser group (7.75±2.40 vs. 21±4.45 days, p<0.01). Complications such as secondary bleeding in 4 (20%) patients, urinary retention in 5 (25%) patients and anal stenosis in 5 (25%) patients occurred only in the open group. Conclusion: Laser haemorrhoidoplasty offers significant advantages over Milligan-Morgan haemorrhoidectomy, including reduced pain, faster recovery, and fewer complications.